Association of Interleukin-6 Levels and Futile Reperfusion After Mechanical Thrombectomy. (2nd February 2021) - Mechtouff, Laura; Bochaton, Thomas; Paccalet, Alexandre; Da Silva, Claire Crola; Buisson, Marielle; Amaz, Camille; Derex, Laurent; Ong, Elodie; Berthezene, Yves; Eker, Omer Faruk; Dufay, Nathalie; Mewton, Nathan; et al.
Abstract : Objective: To assess whether interleukin-6 (IL-6) level is a marker of futile reperfusion in patients with acute ischemic stroke (AIS) with large vessel occlusion treated with mechanical thrombectomy (MT). Methods: The Cohort of Patients to Identify Biological and Imaging Markers of Cardiovascular Outcomes in Stroke (HIBISCUS-STROKE) includes patients with AIS treated with MT after MRI. We performed a sequential assessment of IL-6 (admission, 6 hours, 24 hours, 48 hours and 3 months from admission). Among patients with successful reperfusion (Thrombolysis in Cerebral Infarction scale 2b/3), reperfusion was considered effective if 3-month modified Rankin Scale (mRS) score was 0 to 2 and futile if 3-month mRS score was 3 to 6. Our model was adjusted for the main confounding variables. Results: One hundred sixty-four patients represent the study population. One hundred thirty-three patients had successful reperfusion (81.1%), while in 46 (34.6%), reperfusion was classified as futile. In single-variable analyses, high IL-6 levels at 6, 24, and 48 hours in combination with a higher age, a prestroke mRS score >2, a history of hypertension or diabetes, lack of current smoking, a higher baseline NIH Stroke Scale score, the absence of associated intravenous thrombolysis, an intracranial internal carotid artery or a tandem occlusion, and an increased infarct growth were associated with futile reperfusion. After multivariable analyses, a high IL-6 level at 24 hours (odds ratio 6.15, 95% confidence interval 1.71–22.10) remained associated with futile reperfusion. Conclusions: IL-6 is a marker of futile reperfusion in the setting of MT.